Static and dynamic acute stretching effect on gymnasts' speed in vaulting - Siatras, T.; Papadopoulous, G.; Mameletzi, D.; Gerodimos, V.; Kellis, S. (Pediatric Exercise Science, 2003)
Although warm-up and stretching exercises are routinely performed by gymnasts, it is suggested that stretching immediately prior to an activity might affect negatively the athletic performance. The focus of this investigation was on the acute effect of a protocol, including warm-up and static and dynamic stretching exercises, on speed during vaulting in gymnastics. Eleven boys were asked to perform three different protocols consisting of warm-up, warm-up and static stretching and warm-up and dynamic stretching, on three nonconsecutive days. Each protocol was followed by a "handspring" vault. One-way analysis of variance for repeated-measures showed a significant difference in gymnasts' speed, following the different protocols. Tukey's post hoc analysis revealed that gymnasts mean speed during the run of vault was significantly decreased after the application of the static stretching protocol. The findings of the present study indicate the inhibitory role of an acute static stretching in running speed in young gymnasts.